Development and Validation of High-Content Analysis for Screening HDAC6-Selective Inhibitors. (June 2021) - Nong, Yunhong; Hou, Yanyan; Pu, Yuting; Li, Si; Lan, Yan
Throughout recent decades, histone deacetylase (HDAC) inhibitors have shown encouraging potential in cancer treatment, and several pan-HDAC inhibitors have been approved for treating malignant cancers. Numerous adverse effects of pan-HDAC inhibitors have been reported, however, during preclinical and clinical evaluations. To avoid undesirable responses, an increasing number of investigations are focusing on the development of isotype-selective HDAC inhibitors. In this study, we present an effective and quantitative cellular assay using high-content analysis (HCA) to determine compounds' inhibition of the activity of HDAC6 and Class I HDAC isoforms, by detecting the acetylation of their corresponding substrates (i.e., α-tubulin and histone H3). Several conditions that are critical for HCA assays, such as cell seeding number, fixation and permeabilization reagent, and antibody dilution, have been fully validated in this study. We used selective HDAC6 inhibitors and inhibitors targeting different HDAC isoforms to optimize and validate the capability of the HCA assay. The results indicated that the HCA assay is a robust assay for quantifying compounds' selectivity of HDAC6 and Class I HDAC isoforms in cells. Moreover, we screened a panel of compounds for HDAC6 selectivity using this HCA assay, which provided valuable information for the structure–activity relationship (SAR). In summary, our results suggest that the HCA assay is a powerful tool for screening selective HDAC6 inhibitors.